Pelatihan Pembuatan Kerajinan Ecoprint dengan Teknik Pounding bagi Orangtua Murid dan Guru-Guru di Paud Bambim Al Muttaqien - Salma Hasna Hanifah; Mujnitri Yasni; Afriani Kusumadewi; Luciana; Feny Nurherawati; Filly Pravitasari; Tiara Nurhuda; Rini Siskayanti; Lia Muliati; Rani Pramudyo Ningtyas (ABDIMAS Iqtishadia, 2024)
The ecoprint technique is a technique of printing on fabric using natural dyes and making motifs from leaves manually by sticking them until the motif appears on the fabric. One of the coloring techniques in eco-print is the punching or pounding technique. This technique is considered simpler and easier to practice in everyday life. This community service activity was carried out to provide training in ecoprint pounding technique skills, provide botanical insight about leaves that have good traces using the pounding ecoprint technique, and provide entrepreneurial insight so that participants can utilize the pounding ecoprint technique to earn additional income. This service activity was carried out at Paud Bambi Al Muttaqieun which is located on Jalan Muara Selatan I No.17, Pelindung Hewan, Kecamatan Astanaanyar, Bandung City, West Java 40243. The activity was attended by 21 people including Paud teachers, parents, lecturers and student representatives. The training methods used are the lecture method, presentation method and documentation. The result of this training is that participants can apply ecoprint using the pounding technique, apart from that, the results of varying the layout of the leaf motif based on the tastes of the training participants look unique and beautiful with colors that match the original color of the leaves used.